2014
DOI: 10.1155/2014/654198
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-Targeted Antioxidant Prevents Cardiac Dysfunction Induced by Tafazzin Gene Knockdown in Cardiac Myocytes

Abstract: Tafazzin, a mitochondrial acyltransferase, plays an important role in cardiolipin side chain remodeling. Previous studies have shown that dysfunction of tafazzin reduces cardiolipin content, impairs mitochondrial function, and causes dilated cardiomyopathy in Barth syndrome. Reactive oxygen species (ROS) have been implicated in the development of cardiomyopathy and are also the obligated byproducts of mitochondria. We hypothesized that tafazzin knockdown increases ROS production from mitochondria, and a mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 60 publications
2
43
0
Order By: Relevance
“…These cellular models facilitated the understanding of modes of tafazzin dysfunction and provided mechanistic insights regarding the phenotypic heterogeneity seen in BTHS [33] [34]. Other studies involved cellular models such as fibroblasts [35], lymphoblasts [36], neutrophils [37], neonatal ventricular fibroblasts [38], and cardiac myocytes [39]. Later, mouse models were generated and revealed multiple cardiac and muscle dysfunctions [40,41] and disruption of the interactions between the electron transport chain (ETC) and some fatty acid oxidation enzymes [42].…”
Section: Discussionmentioning
confidence: 99%
“…These cellular models facilitated the understanding of modes of tafazzin dysfunction and provided mechanistic insights regarding the phenotypic heterogeneity seen in BTHS [33] [34]. Other studies involved cellular models such as fibroblasts [35], lymphoblasts [36], neutrophils [37], neonatal ventricular fibroblasts [38], and cardiac myocytes [39]. Later, mouse models were generated and revealed multiple cardiac and muscle dysfunctions [40,41] and disruption of the interactions between the electron transport chain (ETC) and some fatty acid oxidation enzymes [42].…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondria targeted antioxidants therapies could be potential treatment for a number of pathologic conditions including neurodegenerative or metabolic diseases. Recently, in vivo and in vitro studies done in experimental animals and humans, reported ameliorative role of mitochondria targeted antioxidants against metabolic disorders [209-212]. The commonly used vitamins (vitamin E and C) and other chemical compounds with antioxidant properties such as coenzyme Q, a-lipoic acid, N-acetylcysteine (NAC) have been used to reduce the excess generation of ROS in various metabolic conditions [213-215].…”
Section: Mitochondria-targeted Antioxidantsmentioning
confidence: 99%
“…64 Injecting animals with a mitochondria-targeted antioxidant, mitoTEMPO, prevented diabetic-associated diastolic dysfunction. 65 Other mitochondria-targeted antioxidants that have shown beneficial effects in muscle include MitoQ10 66 and the mitochondria-selective peptide, SS-31. 67 Any of these may represent a novel therapeutic strategy for diastolic dysfunction.…”
Section: Novel Therapeutic Strategiesmentioning
confidence: 99%